Semantics and syntax: The nominal syntagma in an English-Spanish contrastive study - Noelia Ramón García (Miscelánea: A Journal of English and American Studies, 2002)
In this article we are going to analyse the formal representation of the semantic function of characterisation in English and Spanish. We describe characterisation as the qualitative modification of nouns within the nominal syntagm. The empirical data used for this study have been extracted from the two largest reference corpora for the two working languages, Cobuild and CREA (Corpus de Referencia del Español Actual). First, we have determined the most frequently employed grammatical resources for noun modification in these two languages. In a second part, the data have been analysed from a syntactic point of view in order to try to establish the relationship between the characterisation and the syntactic function of the characterised nominal syntagma, and the possible differences in this aspect between English and Spanish.